REPRESENTATION OF WOMEN IN EIGHTEENTH CENTURY MURAL PAINTINGS OF ODISHA: A SPECIAL FOCUS ON PAINTINGS OF BIRANCHINARAYAN TEMPLE OF GANJAM - Malik, Dr Sankarsan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Painting culture of Odisha has in relation to her social and religious life. Since prehistoric times, Odisha has witnessed the advancement of this visual art. As literature, the painting of the medieval Odisha has obtained great success. Contemporary temples and Mathas in Odisha present wall paintings on the topic of epics and secular ideologies. However, while studying the history of women in medieval Odisha, the painting of the time is the key source to make an authentic framework on this subject. Historical data from that time do not provide sufficient information about the contributions, roles, and status of women in society. The mural paintings of the eighteenth century, mainly in the Ganjam region of Odisha, reflect the social, religious, and cultural life of women. Biranchinarayan temple painting is one of the finest mediaeval paintings in the area. The stories of Ramayana and Mahabharata are vivid depictions on the walls of this temple of the sun. However, portraying female figures in these murals also sheds light on their status and positions in society. The painting of the Rama–Sita wedding ceremony on the wall of this Biranchinarayan temple is the best part of all the murals. Odia traditions, dress styles and wedding ceremonies are reflected in Ramayana’s paintings. The monogamy culture of medieval Odisha is mostly highlighted.